Development of Competence of Teachers of School Biology Regarding the Use of the Distance Learning Platform - Khushnud Nurmetov; Oygul Rasulova (Academia One Publishing, 2023)
The article describes the importance of research and analysis of school biology teachers in improving the quality and effectiveness of education in the system of continuing education based on the distance learning platform, the application of new approaches to distance and traditional learning
Keywords: continuing education process; distance learning; advanced training